Epistatic and Independent Effects on Schizophrenia-Related Phenotypes Following Co-disruption of the Risk Factors Neuregulin-1 × DISC1 - Mitchell, Kevin (My University, 2017)
Few studies have addressed likely gene × gene (ie, epistatic) interactions in mediating risk for schizophrenia. Using a preclinical genetic approach, we investigated whether simultaneous disruption of the risk factors Neuregulin-1 (NRG1) and Disrupted-in-schizophrenia 1 (DISC1) would produce a disease-relevant phenotypic profile different from that observed following disruption to either gene alone. NRG1 heterozygotes exhibited hyperactivity and disruption to prepulse inhibition, both reversed by antipsychotic treatment, and accompanied by reduced striatal dopamine D2 receptor protein expression, impaired social cognition, and altered glutamatergic synaptic protein expression in selected brain areas. Single gene DISC1 mutants demonstrated a disruption in social cognition and nest-building, altered brain 5-hydroxytryptamine levels and hippocampal ErbB4 expression, and decreased cortical expression of the schizophrenia-associated microRNA miR-29b. Co-disruption of DISC1 and NRG1, indicative of epistasis, evoked an impairment in sociability and enhanced self-grooming, accompanied by changes in hypothalamic oxytocin/vasopressin gene expression. The findings indicate specific behavioral correlates and underlying cellular pathways downstream of main effects of DNA variation in the schizophrenia-associated genes NRG1 and DISC1.
Keywords: schizophrenia; Disrupted-in-schizophrenia 1 (DISC1); Endophenotypes; Gene × gene interaction; Genetic mouse model; Psychosis